"[A]n Imaginary Feast": Hospitality and Health in Margaret Cavendish's Alimentary Poetics. Issue 4 (2nd October 2022) - Jacob, Christine
ABSTRACT: As previous scholarship has observed, Margaret Cavendish's ambitious intellectual project—spanning subjects as dissimilar as fairies and fevers—is driven by fancy, an inherently speculative mode of thought, and her correlation of fancy to women's work is a stratagem that licenses her writing. Beginning with the evocative image of Cavendish as the host(ess) of "an Imaginary Feast, " however, this essay argues that the pervasive alimentary conceit is not merely functional but that it illuminates the essential materiality of fancy as an object that is produced, consumed, and incorporated via the matter and motions of the mind and body. Cavendish intimates a poetics that is shaped by Galenic dietetics and the holistic view of health that she expounds in her treatises on natural philosophy. Drawing on the symbolism and currency of recipe form and customs of hospitality, Cavendish demonstrates, especially in Poems and Fancies and with regards to poetry, that fancy's effects are substantial and potentially salubrious.